2022
DOI: 10.1007/s00704-022-04052-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential signal of change among multiple components of West African rainfall

Abstract: Rainfall components likely differ in the magnitude and direction of their long-term changes for any given location, and some rainfall components may carry a greater regional signal of change than rainfall totals. This study evaluates the magnitude of change of multiple rainfall components relative to other components, and the greatest regions of change across all rainfall components in West Africa. Hourly rainfall data from the ERA5 reanalysis dataset was used to derive twelve rainfall components, which were e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Decreasing precipitation trends in the Congo Basin have been reported in many studies in the last two decades (Hua et al, 2016;Jiang et al, 2019;Obarein & Lee, 2022). Other proxies, such as rainforest greenness (Zhou et al, 2014) and cloud cover (Lee, 2020), have also shown decreasing trends.…”
Section: Tropical Land and Ocean Contrast In The Sign And Magnitude O...mentioning
confidence: 89%
See 2 more Smart Citations
“…Decreasing precipitation trends in the Congo Basin have been reported in many studies in the last two decades (Hua et al, 2016;Jiang et al, 2019;Obarein & Lee, 2022). Other proxies, such as rainforest greenness (Zhou et al, 2014) and cloud cover (Lee, 2020), have also shown decreasing trends.…”
Section: Tropical Land and Ocean Contrast In The Sign And Magnitude O...mentioning
confidence: 89%
“…Reanalysis datasets can mitigate these problems by providing homogenous and consistent long-term data on regularly spaced temporal and spatial intervals. Most evaluations of ERA5 reanalysis precipitation dataset show high performance in outperforming other reanalysis and satellitebased products (Centella-Artola et al, 2020;Gleixner et al, 2020;Jiao et al, 2021;Malayeri et al, 2021;Nogueira, 2020;Obarein & Lee, 2022;Randriatsara et al, 2022;Wang & Zhao, 2022, and others). This high performance has led to the growing use of the ERA5 dataset in precipitation trend analysis (e.g., Boisvert et al, 2023;Box et al, 2019;Chinita et al, 2021;Yu & Zhong, 2021).…”
Section: Era5 Reanalysis Precipitation Datasetmentioning
confidence: 99%
See 1 more Smart Citation